(untitled) (Research, Society and Development, 2022)
Objective: Identify in scientific literature the assistance provided the pregnant women given the risk of infection by the new coronavirus and its consequences. Method: Integrative literature review carried out in the SciELO, LILACS and MEDLINE, by crossing the following descriptors: "Nursing care", "Pregnant women", "Prenatal" and " COVID-19”, that addressed the theme, in the last five years, through the Boolean operator “AND” with the inclusion criteria related to Portuguese and English, and publications available in full and free of charge in the aforementioned databases. And as exclusion criteria, studies that did not address the topic, in addition to publications repeated in more than one database. Results and Discussions: After search strategy, 13 articles were obtained for the study. COVID-19 is a public health emergency, first reported in 2019, transmitted by droplets and aerosols expelled by sneezing. Pregnant women were considered as a risk group, as they presented a decrease in the immune system during pregnancy. Therefore, prevention measures were adopted with the aim of minimizing the spread of the virus. Final considerations: This review mapped the information available, so far, on the care provided to women during pregnancy during the pandemic period. It was also observed how social media can help in the prevention of covid-19, it highlighting the important role of the support network for pregnant women during this period and the importance of conducting prenatal care and monitoring throughout the prenatal work. childbirth, childbirth and postpartum.